Effect of Current and Coating Time on the Layer Thickness and Corrosion Rate of Electroplated AISI 1045 - Afira Ainur Rosidah; Vuri Ayu Setyowati; Miftahul Choir (LPPM ITK, 2021)
Corrosion mostly occurs on carbon steel which is applied for automotive components and household needs. This natural phenomenon is impossible to be avoided. However, it can be set by escalating its corrosion initiation time. Electroplating is a method that can be used to give protection to slower the corrosion initiation time by forming a layer on the specimen surface, additionally, this method is simple and low cost. One of the most commonly used metals for electroplating is nickel, nickel electroplating is suitable for automotive component coating. For these reasons, this study is focused on analyzing the effect of current and coating time on the layer thickness and corrosion rate of AISI 1045 carbon steel with nickel electroplating. The current variations used were 0.5; 1.0; and 1.5 A and the coating time variations were 5, 10, and 15 minutes. AISI 1045 was used as the cathode, nickel was as the anode, and nickel chloride was the electrolyte solution. The specimen with a current of 1.5 A and a coating time of 15 minutes shows the thickest coating and the lowest corrosion rate, with values of 0.0205 mm and 0.94 mpy, respectively. This study indicates that the increase of the current and coating time enhances the layer thickness and declines the corrosion rate.